Solution of a Linear Second-Order Differential Equation with Coefficients Analytic in the Vicinity of a Fuchsian Zero Point - Kruglov, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain a solution of a second-order differential equation with coefficients analytic near a Fuchsian zero point. This solution is expressed via the hypergeometric functions and the fractional-order hypergeometric functions introduced in this paper.